2020
DOI: 10.1038/s41467-020-19878-4
|View full text |Cite
|
Sign up to set email alerts
|

Transcription-dependent cohesin repositioning rewires chromatin loops in cellular senescence

Abstract: Senescence is a state of stable proliferative arrest, generally accompanied by the senescence-associated secretory phenotype, which modulates tissue homeostasis. Enhancer-promoter interactions, facilitated by chromatin loops, play a key role in gene regulation but their relevance in senescence remains elusive. Here, we use Hi-C to show that oncogenic RAS-induced senescence in human diploid fibroblasts is accompanied by extensive enhancer-promoter rewiring, which is closely connected with dynamic cohesin bindin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 73 publications
(138 reference statements)
10
59
0
Order By: Relevance
“…In previous Hi-C studies, an increase in long-range interaction between H3K9me3 regions during senescence has been correlated with the detachment of the H3K9me3 regions from nuclear lamina, reduced interaction within the H3K9me3 regions, and SAHF formation (clustering of the H3K9me3 regions) 31,[46][47][48] . Consistently, in our recently generated in situ Hi-C data in proliferative and RIS IMR90 cells 49 , we observed that increased chromatin contacts during RIS tended to be longer-range compared to decreased contacts, which were mostly short distance ( Supplementary Fig. 4A, B).…”
Section: Multiple Mechanisms Might Be Involved In Decompaction Of H3ksupporting
confidence: 89%
See 1 more Smart Citation
“…In previous Hi-C studies, an increase in long-range interaction between H3K9me3 regions during senescence has been correlated with the detachment of the H3K9me3 regions from nuclear lamina, reduced interaction within the H3K9me3 regions, and SAHF formation (clustering of the H3K9me3 regions) 31,[46][47][48] . Consistently, in our recently generated in situ Hi-C data in proliferative and RIS IMR90 cells 49 , we observed that increased chromatin contacts during RIS tended to be longer-range compared to decreased contacts, which were mostly short distance ( Supplementary Fig. 4A, B).…”
Section: Multiple Mechanisms Might Be Involved In Decompaction Of H3ksupporting
confidence: 89%
“…6E, right) 57,58 , reinforcing the functional relevance of the unique mechanism for senescence-specific activation of genes that are otherwise tightly silenced within K3K9me3 regions. Interestingly, we recently identified a similar TAD disruption, in which genes, best exemplified by NRG1 (encoding a SASP factor), can escape from H3K27me3 repressive 3D environment during RIS 49 . Indeed, ChIP-seq data showed a reduction of H3K27me3 in this region ( Supplementary Fig.…”
Section: Multiple Mechanisms Might Be Involved In Decompaction Of H3kmentioning
confidence: 97%
“…Inactivation of CTCF usually leads only to partial disruption of chromatin loops and recruiting of cohesin complexes [ 72 , 88 ]. During cell senescence, cohesion binds to chromatin independently from CTCF and form new chromatin loop domains associated with highly active genes [ 89 ]. To date, only a few proteins have been described that can potentially participate in the organization of chromosome architecture in mammals [ 11 ].…”
Section: Mechanisms Of Distance Interaction Between Enhancers and mentioning
confidence: 99%
“…Are they specific to senescence or even only to OIS? As mentioned earlier, the high-order chromatin environment of the IL1 locus is highly different between acute and chronic inflammatory conditions in fibroblasts, the latter represented by OIS (7). Is DOT1L involved in acute inflammation?…”
mentioning
confidence: 89%